Temporal body and timeless sexuality: a conflict in old age (Research, Society and Development, 2022)
Aging implies body changes, in contrast to other elements that do not change over time, such as sexuality. This happens because it is possible to notice two distinct times - chronological and kairological. The body follows the chronological rhythm, and sexuality, considering its broad sense, does not follow a temporal marking. Faced with this paradox, the objective of this study is to understand the duality experienced in old age, in which there is a body that changes through aging, while desire does not. Based on a theoretical study, from a conceptual review, the methodological course took place in the following order: a brief philosophical understanding of time; a description of the aging body; conceptualization of sexuality in old age; and in the last topic, the ideas presented were brought together, reflecting upon the perspective of the different experience of sexuality between genders in old age. The psychoanalysis theory was the reference adopted to support the discussion. As the male and female body changes, many believe that with the recurrence of flaccid erection in men and women who have started menopause, sexuality and desire is doomed to an end. Elderly people no longer have their body socially recognized and are no longer seen as objects of desire. However, being old is to be desiring but society condemns this perspective due to the taboo of sexualizing seniors and, as a result, making them be seen as asexuals. Thus, the elderly end up repressing themselves as manifestations of pleasure for not understanding their role in this stage of life.